Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.nuclphysa.2014.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Quantum mechanical model for J/ψ suppression in the LHC era

Abstract: We discuss the interplay of screening, absorption and regeneration effects, on the quantum mechanical evolution of quarkonia states, within a time-dependent harmonic oscillator (THO) model with complex oscillator strength. We compare the results with data for R AA /R AA (CNM) from CERN and RHIC experiments. In the absence of a measurement of cold nuclear matter (CNM) effects at LHC we estimate their role and interpret the recent data from the ALICE experiment. We also discuss the temperature dependence of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…We use the hydrodynamical expansion under conservation of the initial entropy S 0 which determines the temperature evolution according to s(T)V(τ) = S 0 = const., where for the entropy density we use a fit to lattice QCD data from Reference [52].…”
Section: Nonequilibrium State With Condensate Formationmentioning
confidence: 99%
“…We use the hydrodynamical expansion under conservation of the initial entropy S 0 which determines the temperature evolution according to s(T)V(τ) = S 0 = const., where for the entropy density we use a fit to lattice QCD data from Reference [52].…”
Section: Nonequilibrium State With Condensate Formationmentioning
confidence: 99%
“…Beraudo et al [20] have interpreted that the imaginary part in the real-time potential arises due to the collisions of the heavy quarks with the light fermions of the thermal bath, whereas Laine et al [21] have measured the thermal imaginary part of real-time static potential from classical lattice gauge theory simulations. Margotta et al [22] have investigated quarkonium states in a complex-valued potential and determined the dissociation temperature of the ground state and first excited states considering both real and imaginary part of the binding energy of quarkonia when immersed in QGP, whereas Pena et al [23] have discussed the role of static screening and absorption/regeneration kinetics in the quarkonium time evolution by employing the time-dependent harmonic oscillator model and the temperature dependence of the real and imaginary parts of the oscillator frequency. Solana et al [24] have shown that the complex potential is much more effective in suppressing quarkonia states than the real one.…”
Section: Introductionmentioning
confidence: 99%